Mineralogy and rheology of raw and activated Turonian to Coniacian clays from Benue Trough, northeastern Nigeria - A.S. Arabi; B.B.M. Dewu; M.O.A. Oladipo; I.I. Funtua (Egyptian Journal of Petroleum)
Since the discovery of oil and gas in Oloibiri, an onshore oilfield located in Oloibiri in Ogbia Local Government Area of Bayelsa State, Nigeria on Sunday 15th January 1956 by Shell Darcy, hundreds of oil wells have been drilled and not a single of these oil wells was drilled without the use of bentonite. This work is aimed at evaluating the rheological properties of raw and beneficiated Nigerian clays to ascertain their worth for use as drilling mud in oil and gas well drilling. This will save foreign earnings used in the importation of bentonite by the oil and gas development companies, create employment opportunity and open a new frontier for solid mineral development. Five clay samples from Pindiga Formation in Benue Trough, northeastern Nigeria were collected and subjected to elemental, rheological and other physical properties tests and analysis, while another portion of same samples were beneficiated using sodium carbonate, gum Arabic and poly-anionic cellulose for rheological enhancement then subjected to same cycle of tests and analysis above. Results obtained indicates that wet beneficiation as adopted in this study has proved to be more effective in Ca and Na ionic exchange. The rheological and other physical properties of the clays attained the standard that is required for use in oil and gas well drilling after addition of 12% sodium carbonate and 1.5 g poly-anionic cellulose. It was also discovered that when the formulation was allow to age (stay for 24 h), it attained optimum rheological requirement with 12% sodium carbonate and just 0.8 g poly-anionic cellulose. The clays studies do not require addition of weighing additive such as barite because of their high iron content which made their density attain the require standard even without additives. Keywords: Bentonitic clay, Beneficiation, Nigeria, Pindiga, Rheology, Mineralogy